THEORETICAL FOUNDATIONS OF INTERNATIONAL PROGRAMS IN EDUCATIONAL CONTENT - Asqaralieva Muxtasar Azizjon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the main purpose, mission, plan of the International Assessment Study. The importance of the TIMSS international study in improving the effectiveness of mathematics has been highlighted.